ON HOMOMORPHISM AND ISOMORPHISM OF ALGEBRAIC STRUCTURES - Mamadaliev BM (International Journal on Integrated Education, 2023)
The concepts of algebraic structure extension, algebraic structure homomorphism and isomorphism were introduced, rules, ideas were considered.